Upaya Meningkatkan Aspek Kognitif Melalui Media Papan Angka Bagi Anak Usia 4–5 Tahun Di TK Negeri Malawona - Dhi, Bibiana; Ita, Efrida; Dhiu, Konstantinus Dua; Ngura, Elisabeth Tantiana (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to improve the cognitive aspects of children aged 4-5 years in TK Negeri Malawona through the use of number board media. The method used is Classroom Action Research (CAR) model Kemmis and McTaggart which is implemented in two cycles. The research instruments include observation sheets and documentation. Data analysis is carried out qualitatively and quantitatively. The results of the study showed a significant increase in children's cognitive abilities after the application of the number board media. In the early stages (pre-test), only 31% of children were in the "developing as expected" (BSH) category. After cycle II, there was an increase to 77% of children in the BSH category and 23% in the "developing very well" (BSB) category. Number board media has been proven effective in improving the ability to recognize numbers, strengthening basic arithmetic skills, and increasing children's interest and active participation in learning. This study recommends the use of concrete media such as number boards as a fun numeracy learning strategy that is in accordance with the developmental stages of early childhood.